A REVIEW ON AYURVEDA MANAGEMENT OF SOMNAMBULISM IN CHILDREN - Chaudhari Swapnil Subhash (International Journal of Applied Ayurved Research, 2019)
Sleep is a condition of body and mind which typically recurs for several hours every night, in which nervous system become inactive, eyes closed, the postural muscles relaxed and consciousness practically suspended. Sleep plays a vital role in good health and well being throughout the life. In Ayurveda literature , Nidra is mentioned one among three pillars of life which plays an important role in maintaining health , proficiency and emotional well-being. Sleep disorders are problem with sleeping including trouble in falling or staying asleep, falling asleep at wrong time or place or abnormal behaviour during sleep like talking or walking in sleep. Sleep walking is a sleep disorder belonging to Parosomnia family. Sleepwalker arise from the slow wave sleep stage in a stage of low consciousness and perform activities that are usually performed during a state of full consciousness .These activity can be as benign as sitting up in bed , walking to bathroom or as hazardous as running , violent gestures , grabbing at hallucinated objects or even homicides. According to national sleep foundation , benzodiazepines like Clonazepam reduces the episodes but the recurrence of episodes demands an alternative approach of medicine. There is no direct reference for sleep walking in Ayurveda but the treatment of insomnia can be given to children suffering with somnambulism in order to reduce the episodes of sleep walking and to improve the quality of sleep.